2001
DOI: 10.1093/humrep/16.7.1359
|View full text |Cite
|
Sign up to set email alerts
|

Absent biologically relevant associations between serum inhibin B concentrations and characteristics of polycystic ovary syndrome in normogonadotrophic anovulatory infertility

Abstract: In conclusion, inhibin B serum concentrations are normal in WHO 2 and PCOS women, suggesting a normal number of healthy early antral follicles despite increased overall follicle numbers in PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
31
2
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 20 publications
8
31
2
4
Order By: Relevance
“…It was previously shown that, similar to ovaries of healthy women, inhibin B is the predominant form of inhibin in the follicular fluid of polycystic ovaries and each individual follicle in PCOS produces a similar amount of inhibin B to that secreted by small antral follicles in normally cycling women [10]. Taken together with the fact that we found similar serum concentrations of inhibin B in the early follicular phase in ELF patients and controls, which is in line with the results of previous reports [1,13], this suggests certain mechanisms within the follicles that concentrate and sequester hormones in the follicular fluid. The idea of individual hormone-dependent transport mechanisms is further corroborated by the finding that the ratio between follicular fluid and serum levels is different for E 2 , inhibin A, and inhibin B [7].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…It was previously shown that, similar to ovaries of healthy women, inhibin B is the predominant form of inhibin in the follicular fluid of polycystic ovaries and each individual follicle in PCOS produces a similar amount of inhibin B to that secreted by small antral follicles in normally cycling women [10]. Taken together with the fact that we found similar serum concentrations of inhibin B in the early follicular phase in ELF patients and controls, which is in line with the results of previous reports [1,13], this suggests certain mechanisms within the follicles that concentrate and sequester hormones in the follicular fluid. The idea of individual hormone-dependent transport mechanisms is further corroborated by the finding that the ratio between follicular fluid and serum levels is different for E 2 , inhibin A, and inhibin B [7].…”
Section: Discussionsupporting
confidence: 93%
“…Some authors reported raised concentrations of total immunoreactive inhibins [19], α-inhibin [9,13] or inhibin B [20,21,22], supporting the above hypotheses, while others observed normal levels of total immunoreactive inhibin [12] or inhibin B [1,10,13,23] in the early follicular phase.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations